Investigating the effects of fiber surface treatment and alignment on mechanical properties of recycled carbon fiber composites. (April 2019) - van de Werken, Nekoda; Reese, Malcolm S.; Taha, Mahmoud R.; Tehrani, Mehran
Abstract: Recycled carbon fibers cost a fraction of virgin fibers and their composites can potentially achieve mechanical properties suitable for a wide range of applications. When recycled, carbon fibers usually become millimeter to centimeter long and emerge as a tangled mass analogous to cotton candy. In this work, recycled carbon fibers were processed into unidirectionally aligned and two-dimensional randomly oriented recycled carbon fiber mats. The surface of the recycled carbon fibers was probed to understand the significance of surface characteristics on the mechanical behavior of recycled carbon fiber composites. Tensile testing was used to determine the influence of fiber surface quality, aspect ratio, and alignment on mechanical properties of the composites. It is concluded that the processing has a significant effect on the properties of recycled fiber composites. An analytical model was validated and subsequently used to provide insight into viable methods for improving mechanical properties in recycled carbon fiber composites.